Tingkat Pengetahuan Wanita Pra Lansia Tentang Menopause Di Desa Pantan Lues Kecamatan Gajah Putih Kabupaten Bener Meriah Tahun 2017 - Nurcahaya nainggolan; Nurlela Petra Saragih; Desy Lustiyani Rajagukguk (Universitas Sari Mutiara Indonesia, 2023)
Menopause is a natural physical transition for every woman as she gets older and is often interpreted as the last menstrual stop in a woman's life, which is a slow process and occurs gradually. Women begin to experience menopausal symptoms in their 40s, the peak occurs at the age of 50 when during menopause women no longer experience menstruation. This study aims to identify the level of knowledge of women when facing menopause. Menopause is the physiological cessation of the menstrual cycle which is related to the elderly level of women. A woman experiencing natural menopause has absolutely no way of knowing whether a particular menstrual period is really her last until a year has passed. Menopause is sometimes referred to as the change of life. This research is descriptive in nature which describes the knowledge of pre-elderly women on menopause in the village of Pantan Lues Kec. White Elephant Kab. Bener Meriah 2017. The sampling technique in this study was based on total sampling with a total of 49 respondents. The results of the study. Knowledge of pre-elderly women about menopause, the majority of elderly people have sufficient knowledge, namely 44 respondents (89%), and a minority with less knowledge, namely as many as 3 respondents (4%) in Pantan Lues Village, Kec. White Elephant Kab. Bener Meriah Year 2017. It is suggested to educational institutions to further improve learning about menopause material so that it can be applied in society later and it is hoped that future researchers can become useful information for future researchers so that they can develop research on knowledge of pre-elderly women on menopause.